Seasonal Variations in Thermal Perception of Urban Environments: Summer and Winter In-situ Assessment from a Central European Town - Květoňová, Veronika; Pánek, Jiří; Šerý, Miloslav; Lehnert, Michal (Geographica Pannonica, 2025)
Growing urbanisation, together with extreme weather events, negatively affects urban populations worldwide. Recent urban climate studies demonstrate that people-oriented approaches are needed to effectively target adaptation measures and thus improve urban populations’ well-being. In this study we used the in-situ approach of sketch mapping to identify thermally pleasant and unpleasant places during two seasons, summer and winter, in Ústí nad Orlicí, a Czech town. Generally, places perceived as the most thermally unpleasant, regardless of season, are parking lots near shopping centres, and these require priority attention from urban planners. Respondents consistently identified the planting of high greenery and the construction of shelters as preferred adaptation measures across both seasons. Our findings also point to a clear preference for more enclosed places.